Solar Pumping : The Basics - World Bank Group (World Bank, Washington, DC, 2018)
Solar photovoltaic water pumping (SWP) uses energy from solar photovoltaic (PV) panels to power an electric water pump. The entire process, from sunlight to stored energy, is elegant and simple. Over last seven years, the technology and price of solar pumping have evolved dramatically and hence the opportunities it presents. Solar pumping is most competitive in regions with high solar insolation, which include most of Africa, South America, South Asia, and Southeast Asia. This book focuses on the basics of Solar pumping.